Rooted in the past: Historical legacies and memory policy debates in post-authoritarian Portugal - Raimundo, F. (Revista de Estudios Políticos, 2025)
This article examines how memory issues, particularly transitional justice bills, are debated and decided in national parliaments, focusing on the historical roots of political elites and parties. Drawing on the concept of authoritarian successor parties (Loxton, 2015), we argue that the presence or absence of these parties influences the approval of transitional justice laws. In cases where no such parties exist, as in Portugal, we analyze how political parties ideologically aligned with the previous regime —but not directly linked to it— navigate the “authoritarian stigma”. We hypothesize that these parties may support transitional justice bills, even against their preferences, to distance themselves from the authoritarian past. To explore this, we conduct a qualitative analysis of transitional justice bills debated in the Portuguese parliament since 1976, a rare context with no authoritarian successor parties and a strong authoritarian stigma arising from the democratic transition. Our findings reveal that right-wing parties, despite not being successor parties, generally avoid opposing transitional justice bills. The debates also highlight the emergence of a second type of stigma, enriching the understanding of how memory and transitional justice intersect with political legacies.